2008
DOI: 10.1177/0021998307086203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fiber Surface Texture Created from Silane Blends on the Strength and Energy Absorption of the Glass Fiber/Epoxy Interphase

Abstract: Most of the research to date has focused on tailoring the interphase adhesion by controlling the degree of chemical bonding between fiber and resin. The interfacial shear strength (IFSS) has been increased as much as 40% by modified chemical surface bonding [1—3]. However, it is well known that increasing the interfacial strength of the fiber reinforced polymeric composite material often leads to a reduction in the fracture toughness and vice versa [4—12]. In this study, the effects of mechanical interlocking,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 53 publications
1
42
0
1
Order By: Relevance
“…Nanoparticles have been directly incorporated into SCAs [28]. It has been demonstrated that the change in morphology, or texture, of the interphase can improve both strength and energy absorption during fracture [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticles have been directly incorporated into SCAs [28]. It has been demonstrated that the change in morphology, or texture, of the interphase can improve both strength and energy absorption during fracture [28].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the change in morphology, or texture, of the interphase can improve both strength and energy absorption during fracture [28]. Using CNTs at the fiber interface Rausch and Mäder [29] demonstrated that conductive modification with CNTs can be utilized to sense localized fracture at the fiber and interphase levels.…”
Section: Introductionmentioning
confidence: 99%
“…As there is a steadily increasing interest in the use of thermoplastic composites in different fields, such as construction, automotive industries and aeronautic industries, in the field of GF reinforced thermoplastic composites various strategies have been developed in order to tailor the interphase characteristics, which mainly focused on the modification of GF surface or matrix, aiming at enhancing the GF-matrix adhesion strength, such as by enhancing GF-matrix compatibility, mechanical interlocking, and acid-base interaction [1][2][3][12][13][14]. From the viewpoint of production, on-line surface modification of the as-spun GF with an appro-priate sizing (generally a mixture of silane coupling agent, polymeric film former and additives) is a straightforward strategy for tailoring the interphase properties to give cost-effective composite materials [14][15][16][17][18][19][20][21][22][23][24][25]. Thus, great attentions have been paid on the sizing structure or radial chemical composition to deepen the understanding of the correlation between the mechanical properties of composites and both the sizing and sizing technology.…”
Section: Introductionmentioning
confidence: 99%
“…The healing ability of the fiber-resin interface was investigated with single fiber microdroplet pull-out testing [32]. The testing apparatus was constructed in-house at the US Army Research Laboratory and has a maximum load rating of 200 g with a sensitivity of 0.01 g and data collection rate of 1.67 Â 10 À3 s À1 .…”
Section: Microdroplet Single Fiber Pull-out Testingmentioning
confidence: 99%